Zmiany na obszarach wiejskich w Polsce - percepcja, wiedza i zaangażowanie "starych" i "nowych" mieszkańców wsi = Changes in rural areas in Poland - perception, knowledge and commitment of the "old" and "new" rural inhabitants - Herudziński, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article analyses the processes of change in Polish villages, which result from the fact that new residents are settling down in their areas. A signi?cant number of Polish villages is subject to processes resulting from demographic and population changes, which entails cultural and social changes. Drawing on the theoretical concept of ruralization at the empirical level, the author analyses the opinions of the inhabitants of Czarny Las, a village which was treated as an exempli?cation of the previously de?ned processes.
Keywords: zmiana; wieś; obszary wiejskie; mieszkańcy wsi; ruralizacja; deterytorializacja; change; village; rural areas; rural residents; ruralization; deterritorialization